Taxonomic revision of the genus Rhopalapion Schilsky, 1906 (Coleoptera, Apionidae) with description of Rhopalapion celatum n. sp. from the Turanian Region - Giusto, Carlo (Zootaxa, 2021)
The genus Rhopalapion Schilsky, 1906 is revised and its name is applied to Apionidae with elongate body, elongate antennal club and strong sexual dimorphism in the length of rostrum, whose biology is related to Malvaceae belonging to the genus Alcea L., 1753. The morphological study of various populations hitherto attributed to Rhopalapion longirostre (Olivier, 1807) allowed the identification of a further species, Rhopalapion celatum n. sp. (♂♀, type locality: S-Iran: Fars Province: Pâsârgâd: vicinity tomb of Cyrus), distributed in Turkey, Armenia, Azerbaijan, Syria, Iraq, Iran, Uzbekistan, Kyrgyzstan and Kazakhstan. Lectotype (♂) of Apion longirostre Olivier, 1807 is designated. The following new combinations are proposed for the species formerly assigned to Rhopalapion: Pseudaspidapion leptorostre (Voss, 1959) n. comb. and Harpapion coelestipenne (Voss, 1962) n. comb. The genera Anacrapion Mazur, 2011 and Lopatinapion Friedman, 2013 are provisionally removed from the tribe Malvapiini Alonso-Zarazaga, 1990 and considered members of the supertribe Aspidapiitae Alonso-Zarazaga, 1990 with no tribal attribution.